Analytical Study on Fertility Status and Soil Quality Index of Shorearobusta Forest, Central Nepal - Thapa, Mahendra Singh; Bhattarai, Thakur; Sharma, Ram Prasad; K. C, Baburam; Puri, Lila (Tribhuvan University Journal, 2019)
Physiochemical parameters of soil under Shorearobusta forest was estimated to evaluate the soil fertility status and soil quality index in different altitudes of community managed forest of Khairani Municipality Chitwan district Nepal. Altogether 75 soil samples were collected from the forest area at five different depths. Sandy clay loam and sandy loam texture was found in surface and subsurface layer respectively. The mean soil pH of altitudinal strata was 5.57 which is moderately acidic and showed decreasing trend with increasing soil depths. Average bulk density ranged from 1.14 to 1.30 in all attitudes. Organic carbon varied from 0.30 to 1.30% and organic matter ranges from 0.52 to 2.23%. The amount of mean available phosphorus seem low to medium rating in these forest strata. Mean exchangeable potassium varied from 61.89 mg kg-1 to 96.02 mg kg-1 in different altitudes. Most of these soil attributes decreased with the increasing depth. Pearson correlation analysis among the different soil parameters were showed statistically significant at the 0.01 level (2 – tailed) and 0.05 levels (2 - tailed).One way ANOVA of the studied soil parameters in different altitudes observed that they were statistically significant at 0.05 level (p ≤ 0.05). The overall soil fertility status of the Kankali Community Forest is low to medium. An average SQI was found 0.55 (fair) up to 120 cm depths,slightly decreased with increasing soil depths. Regulation of Leaf litter collection and adoption of appropriate silvicultural operation may help to increase the fertility status and site quality of Kankali community forest.